2019
DOI: 10.1152/ajpgi.00343.2018
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling inhibition by monensin results in a period of Hippo pathway activation during intestinal adaptation in zebrafish

Abstract: Intestinal adaptation (IA) is a critical response to increase epithelial surface area after intestinal loss. Short bowel syndrome (SBS) may follow massive intestinal resection in human patients, particularly without adequate IA. We previously validated a model in zebrafish (ZF) that recapitulates key SBS pathophysiological features. Previous RNA sequencing in this model identified upregulation of genes in the Wnt and Hippo pathways. We therefore sought to identify the timeline of increasing cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…After 14 days, SBS fish lost a significant amount of weight compared with Sham fish (75.6 Ϯ 3.1 vs. 97.1 Ϯ 3.9%, P Ͻ 0.0001; Fig. 1, A and B), consistent with prior studies (3,24,48,50). Despite receiving broad-spectrum antibiotics, ShamϩAbx and SBSϩAbx fish displayed similar postoperative weight curves when compared with sham and SBS fish (Fig.…”
Section: Resultssupporting
confidence: 86%
“…After 14 days, SBS fish lost a significant amount of weight compared with Sham fish (75.6 Ϯ 3.1 vs. 97.1 Ϯ 3.9%, P Ͻ 0.0001; Fig. 1, A and B), consistent with prior studies (3,24,48,50). Despite receiving broad-spectrum antibiotics, ShamϩAbx and SBSϩAbx fish displayed similar postoperative weight curves when compared with sham and SBS fish (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Downstream the pathway it was evaluated to role of beta-catenin, and both genetic and protein expressions were restored by the use of LiCl in animals with periodontitis receiving Mon [16,45]. It has been reported that Mon inhibits beta-catenin but LiCl can provide a greater expression of beta-catenin, in turn.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer attributes of monensin are ascribed to its capability to induce oxidative stress and inhibit signaling pathways involving mTOR, MYB, and growth factor receptors. Several studies have reported that monensin exerts inhibitory effects on canonical Wnt/β-catenin signaling [ 21 - 23 ].…”
Section: Introductionmentioning
confidence: 99%